Visualization of Local Ionic Concentration and Diffusion Constants Using a Tailored Electrochemical Strain Microscopy Method. Issue 3 (1st January 2019) - Simolka, M.; Heim, C.; Friedrich, K. A.; Hiesgen, R.
Abstract : A tailored electrochemical strain microscopy technique is presented and used to analyze the ionic mobility and diffusion coefficients in composite Si/C anodes. The resulting surface displacement after a voltage pulse is proportional to the ionic concentration change and is measured by the deflection of an atomic force microscopy tip. The results show a higher ionic mobility at the steps of silicon composite anode microcrystals compared to the crystal centers. Diffusion coefficients are extracted from the time dependence of the surface displacement. Mappings with nanoscale resolution of local diffusion coefficients are displayed. The results demonstrate higher diffusion coefficients at the steps.